The Role of the Publishing Industry in the New Order Era as a Supporter of the Illiteracy Eradication Program in Indonesia - Widayanti, Firda Mutia; Kirana, Lintang Marsashi; Handayani, Tri (Proceedings International Conference of Culture and Sustainable Development; Vol 2 (2024): PROCEEDINGS ICOCAS, 2024)
The eradication of illiteracy during the New Order was a big step, including for the publishing industry in Indonesia. There are not many studies that discuss how the illiteracy eradication program during the New Order affected the growth of the publishing industry. This article aims to show the growth of publishing during the New Order era and its role in the eradication of illiteracy. This article uses the methods of observation and literature study. The sources used are obtained from books, journal articles, and presidential instructions. Then, the sources were analyzed and interpreted for the writing. The results show that the emergence of SD Inpres during the New Order era as a policy in the illiteracy eradication program had an impact on the growth of the publishing industry to help reduce illiteracy in Indonesia. This growth was accompanied by the production of large numbers of books, such as books with cognitive, affective and psychomotor content that encouraged reading skills and developed critical awareness. This development was a step change from the problems left by the VOC and the Dutch East Indies government to the indigenous population, who were restricted in their access to education, especially the lower classes. This left many of them unable to master some basic skills, including reading, which then led to many indigenous people becoming illiterate
Keywords: Illiteracy, New Order, Publishing Industry, Books